Does national ethical judgment matter for earnings management? - Viana, D. B. C., Jr.; Lourenço, I. (Atas do XVI CICA, 2019)
This study analyses the effect of ethical judgment at country-level on earnings management. While previous literature document the role of ethical issues at personal- and organizational-level on earnings management practices, usually theoretically and through qualitative ways, we investigate that association in a large sample at international level taken a sample of 81,408 firm-year observations regarding 10,306 firms from 39 countries. Based on data from an international questionnaire developed by the World Values Survey, we construct a comprehensive index of ethical judgment of each country. Our empirical findings suggest that the level of ethical judgment of the countries are negative associated with accruals-based earnings management, suggesting that the manipulation of accounting amounts is lower in countries where ethically suspect behaviours are less acceptable. Additionally, we also provide empirical evidences that this phenomenon is verified both in developed and emerging countries, and that ethical judgment at country-level seem to moderate the association between IFRS adoption and earnings management practices.